Literature Review : Pengaruh Media Pembelajaran Literasi Visual Terhadap Hasil Belajar Biologi Siswa SMA: (Literature Review: The Influence of Visual Literacy Learning Media on High School Students Biology Learning Outcomes) - Indah, Reski Alma; Fadilah, Muhyiatul (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2024)
The use of visual literacy-based learning media has become an increasingly important topic in education, especially in the context of biology learning at the high school level. This article aims to present a comprehensive literature review on the influence of visual literacy-based biology learning media on improving high school students' learning outcomes. The research method used is a literature review, by analyzing related studies and research, this article presents empirical evidence about the effectiveness of learning media based on visual literacy in improving the understanding and learning outcomes of high school students in biology subjects. It was found that the learning outcomes of students in classes that used visual literacy learning media were higher than those in classes that did not use them. So it is concluded that visual literacy learning media influences student learning outcomes. Abstrak. Penggunaan media pembelajaran berbasis literasi visual telah menjadi topik yang semakin penting dalam pendidikan, terutama dalam konteks pembelajaran biologi di tingkat SMA. Artikel ini bertujuan untuk menyajikan tinjauan literatur yang komprehensif tentang pengaruh media pembelajaran biologi berbasis literasi visual terhadap peningkatan hasil belajar siswa SMA.Metode penelitian yang digunakan yaitu literature review, dengan menganalisis studi dan penelitian terkait, artikel ini menyajikan bukti-bukti empiris tentang efektivitas media pembelajaran berbasis literasi visual dalam meningkatkan pemahaman dan hasil belajar siswa SMA dalam mata pelajaran biologi.Didapatkan hasil belajar siswa kelas yang menggunakan media pembelajaran literasi visual lebih tinggi daripada kelas yang tidak menggunakan. Sehingga disimpulkan bahwa media pembelajaran literasi visual berpengaruh terhadap hasil belajar siswa.